2011
DOI: 10.3109/01443615.2011.590910
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of sperm DNA fragmentation index with the outcomes ofin-vitrofertilisation-embryo transfer and intracytoplasmic sperm injection

Abstract: This study was conducted to investigate the relationship between sperm DNA fragmentation index (DFI) and the outcomes of in-vitro fertilisation-embryo transfer (IVF-ET) and intracytoplasmic sperm injection (ICSI). Sperm DFI in 116 patients for IVF and 63 patients for ICSI were detected with acridine orange test (AOT), and all the cases were divided into DFI ≤ 30% group and DFI > 30% group according to the DFI value; then, the relationship of DFI with the outcomes of IVF/ICSI were analysed. Both in IVF and ICSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…There was no significant difference in the mean age, marital life, body mass index (BMI), semen volume, or abstinence period between DNA fragmentation normal and abnormal groups (Table 1). 35.96 ± 20.01) (P \ 0.001). Similarly, the percentage of abnormal forms was less in the DNA normal group compared to the abnormal group which was significant (90.06 ± 7.12 vs. 92.90 ± 5.55) (P \ 0.001).…”
Section: Resultsmentioning
confidence: 96%
“…There was no significant difference in the mean age, marital life, body mass index (BMI), semen volume, or abstinence period between DNA fragmentation normal and abnormal groups (Table 1). 35.96 ± 20.01) (P \ 0.001). Similarly, the percentage of abnormal forms was less in the DNA normal group compared to the abnormal group which was significant (90.06 ± 7.12 vs. 92.90 ± 5.55) (P \ 0.001).…”
Section: Resultsmentioning
confidence: 96%
“…This suggests that the mode of spermoocyte combination might affect blastocyst development. It is known that sperms with normal morphology and intact acrosomes combine more readily with the zona pellucida, and have superior DNA integrity than abnormal sperms [Jiang et al 2011], suggesting that the the zona pellucida-bound sperm appeared to be superior or more competent than the general population of motile sperm [Liu et al 2011]. In the IVF procedure, the zona pellucida itself appears to be relatively selective for sperm in the process of natural sperm-oocyte combination.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recognized threshold value for DFI has not been established yet, in this work we referred to some recent studies that have indicated: i) 30% as the cut off value above that natural pregnancy is not possible to be achieved [3,24] ii) DFI > 30% provides significantly lower embryo implantation rate and pregnancy rate [25]. These data supported also previous statistical studies indicating that the pregnancy rates were lower in case of DFI over 30% [26] and significantly higher in men with DFI below the thresholds of 30% [27].…”
Section: Discussionmentioning
confidence: 99%